2020
DOI: 10.1016/j.scitotenv.2020.140496
|View full text |Cite
|
Sign up to set email alerts
|

Air quality changes in New York City during the COVID-19 pandemic

Abstract: States was heavily affected by the COVID-19 pandemic. • Linear time lag models show no difference in air quality between 2020 and 2015-2019. • Air quality trends should be considered when gauging short-term pollution changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
145
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(157 citation statements)
references
References 28 publications
10
145
0
2
Order By: Relevance
“… Adams (2020) , focusing on Ontario during the five-week Canadian lockdown, pinpointed a reduction of nitrogen dioxide and nitrogen oxides when compared to the previous 5-week control period. Along the same lines, Zangari et al (2020) noted a decrease of PM 2.5 (36%) and NO 2 (51%) concentrations in New York shortly after the lockdown. The study by Tobías et al (2020) describes the changes in air pollution levels stemming from the measures of containment in Barcelona.…”
Section: Resultsmentioning
confidence: 62%
“… Adams (2020) , focusing on Ontario during the five-week Canadian lockdown, pinpointed a reduction of nitrogen dioxide and nitrogen oxides when compared to the previous 5-week control period. Along the same lines, Zangari et al (2020) noted a decrease of PM 2.5 (36%) and NO 2 (51%) concentrations in New York shortly after the lockdown. The study by Tobías et al (2020) describes the changes in air pollution levels stemming from the measures of containment in Barcelona.…”
Section: Resultsmentioning
confidence: 62%
“…By comparison, there have been reports of substantial decreases in PM 2.5 concentrations due to reduced human activity related to COVID-19 (e.g., Collivignarelli et al [ 16 ]; Kerimray et al [ 7 ]; Li et al [ 13 ]; Lian et al [ 4 ]; Sharma et al [ 15 ]; Zangari et al [ 19 ]). For example, Wuhan, which was subjected to a series of strict lockdown orders, saw a 36.9% decrease in PM 2.5 concentration [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adversely, such reductions may have contributed to the elevated ozone (O 3 ) concentrations in Wuhan and cities in Southern Europe [ 18 ]. On the other hand, social restrictions might not lead to a significant difference in air quality in cities with low baseline concentrations of pollutants such as New York [ 19 ]. Owing to the apparent diversity in the air quality and COVID-19 situations among different regions, a specific case study that takes into account the unique conditions in each city can be helpful.…”
Section: Introductionmentioning
confidence: 99%
“…For policy-making purposes, these figures offer a more realistic scenario, because policymakers should consider long-term variations and different factors that affect them, avoiding misleading artifacts. Using a similar approach, Zangari et al (2020) showed that, even though PM 2.5 and NO 2 concentrations in New York decreased during the lockdown, no reductions were observed in the long-term analysis.…”
Section: Discussionmentioning
confidence: 99%